Hybrid Nanostructures: Programmed Hierarchical Hybrid Nanostructures from Fullerene‐Dendrons and Pyrene‐Dendrons (Small 49/2018). Issue 49 (6th December 2018) - Park, Minwook; Kang, Dong‐Gue; Yoon, Won‐Jin; Choi, Yu‐Jin; Koo, Jahyeon; Lim, Seok‐In; Jeong, Kwang‐Un
Abstract : In article number1803291, Kwang‐Un Jeong and co‐workers show that hierarchical hybrid nanostructures are constructed by the host‐guest complex between the fullerene dendron and pyrene dendron. Based on the consideration of structural motifs and host‐guest interactions, fullerene and pyrene building blocks are successfully programmed and self‐assembled to fabricate sub‐10 nm nanostructures. This new strategy is expected to be a practicable and reasonable guideline for the construction of hierarchical hybrid nanostructures.